If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14 + 4n = 0 Solving 14 + 4n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + 4n = 0 + -14 Combine like terms: 14 + -14 = 0 0 + 4n = 0 + -14 4n = 0 + -14 Combine like terms: 0 + -14 = -14 4n = -14 Divide each side by '4'. n = -3.5 Simplifying n = -3.5
| 16x^2+16y^2+48x-88y+132=0 | | z^3+2z^2+5z+6=0 | | u*0.8=u+1 | | ax^4-a^5b^5=0 | | 12-4x/3-x | | x+-7=0.5x-1 | | x-7=0.5x+1 | | 9-3x=2x | | x+7=0.5x+1 | | f(x+3)=5-7x | | -3x-8=x | | 1/10*n=3 | | (x-2)(x+7)=(x-3)(x-4) | | 2x-3(2+x)=5+x | | 2(x-3)-7(2-x)=x+4 | | 5+2.10x=49.10 | | (X^2)-5=4 | | 7+1.25t=43.25 | | 5=3(1-2x) | | 10-[8-(2x-3)]=2x-5 | | (X+8)*2=20 | | 5=3x(1-2x) | | 1/5x=-1 | | 4x+-1=39 | | 4t+23=265 | | 4y+68=168 | | 4y(5y-7x)+4(7x+8x)= | | 2x+6=3x+12 | | 18+5=299 | | 15+3=216 | | (a-2)/3=(1-a)/2 | | X(x+7)-x-2= |